The Effect of Effectiveness Online Registration System at the Outpatient Polyclinic During the Covid-19 Pandemic - Sapriadi Sapriadi; Yenni Artanti Ziliwu (Jurnal Perilaku Kesehatan Terpadu, 2022)
Online registration with the whatsapp system based on the survey results there are still shortcomings in the online registration service in the online registration service so it is necessary to increase using human resources through technological advancement will also help the service in an integrated manner.  This research is determining the effectiveness of the online registration system at Sundari Hospital.  Cross-sectional quantitative research is the type of study that was used. This study was carried out at the Sundari General Hospital Medan. The population in this study was all patients in the polyclinic room of Sundari General Hospital Medan which amounted to 60 people and all of them were sampled. The data collection instrument uses questionnaires that are distributed directly to respondents. Data analysis using univariate, bivariate and multivariate analysis using simultaneous tests (F-test). Research known that the results of the Chi-Square test on the quality of service to the effectiveness of the online registration system obtained P-Value = 0.000, System Quality to the effectiveness of the P-Value 0.000, the quality of security to the effectiveness of the online registration system P-Value 0.006. Based on the results of the simultaneous test (Test F) a p-value of 0.000 was obtained. In this study, there is an influence simultaneously or simultaneously between the quality of service, system quality, quality of security on the effectiveness of the online registration system at the outpatient polyclinic during the Covid-19 pandemic at the Sundari General Hospital.